PENILAIAN KETERAMPILAN PROYEK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Kana Iftika Wuri; Ubabuddin (CV. ADIBA AISHA AMIRA, 2023)
The scientific approach in learning is carried out through activities to dig up information through observation, ask questions, explore or collect data or information, then process data or information and end by presenting data or information in oral, written or other forms. This approach is inseparable from the objectives of developing the 2013 curriculum that is currently being used. Project-based learning is also believed to be able to encourage students to produce creative and contextual works both at the individual and group levels. Project Assessment is one of the assessment models in skills other than product assessment. However, at certain times the project assessment can also be used as a knowledge assessment. Because of the steps in working on the project students get a real knowledge.